UTILIZING FLASHCARD MEDIA TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT THE SEVENTH GRADE OF MTS BOARDING SCHOOL TAHFIDZ BAITUSY SYAKIRIN - Yuliani Panjaitan, Winda (BRIGHT VISION Journal of Language and Education, 2023)
Vocabulary is the base component of language that needs to be mastered because it covers all of the language skills.To help learners improve their vocabulary mastery, visual media has been reported effective in many studies as media to assist students in mastering vocabulary. Hence, the objective of this research was to know whether utilizing Flashcard Media could also improve the students’ vocabulary mastery at the seventh grade of Junior High School. This research was conducted at MTs Boarding School Tahfidz Baitusy Syakirin which was carried out in the VII-2 class with 20 students. The research design employed was classroom action research with two cycles.In every cycle, the researcher collected qualitative and quantitative data. The qualitative data were obtained from obsevation, interview, and, diary note. While the quantitative data were taken from Pre-Test, Post-Test I,and Post-Test II.Based on the qualitative data, the researcher found three main findings.First,the students gained better understanding and memorizing of the meaning and the writing of the words. Second, the students were more motivated and enjoyed the vocabulary learning, and third, they felt more interested and interested in learning vocabulary. Whereas based on the quantitative data, the researcher found there were 10 students who achieve the Minimum Criteria of KKM score in the post test in cycle I,and 15 students in the post test in cycle II, It can be concluded that students’ scores improved in each test. Thus, it could be concluded that Flashcard Media could be utilized to improve students’ vocabulary mastery.